Analisis pola konsumsi rumah tangga pekerja wanita di Kota Jambi - Inda Pati Sinambela; Zulfanetti Zulfanetti; Etik Umiyati (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2020)
This study aims to determine the expenditure of household consumption of female workers in Jambi City which is influenced by several factors. This research was conducted using a sampling technique that is purposive sampling. The data used in this study were obtained from a questionnaire about household consumption of female workers in Jambi city. The data method analysis used multiple linear regression analysis to determine the effect of wife's income, husband's income, education and the number of family dependents on household consumption of female workers in the city of Jambi. Based on the normality test, the multicollinearity test, and the heteroscedasticity test there were no deviations from the classical assumptions. The results of the research showed that simultaneously the wife's income, husband's income, education and the number of family dependents significantly influence the household consumption of female workers. The partial results showed that the variable of wife's income, husband's income and the number of family dependents have a significant effect, while education has no significant effect on household consumption expenditure of female workers in Jambi City. R-square value of 91.75%, showed that household consumption can be explained by research variables of 91.75%.